Life fragments of Soviet citizens arrived from the PRC for the development of virgin lands - Mazhitova, Zh.S.; Isakhan, G.T. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Based on archival documents, the authors of the article examine the process of repatriation of Soviet citizens from the People’s Republic of China to the virgin lands of Kazakhstan in the 1950s. The study reveals the issues of labour and housing arrangements for immigrants, as well as measures of district authorities to implement the Resolution of the Secretariat of the Regional Committee of the Communist Party of Kazakhstan on the arrangement of citizens arriving from the PRC. Some repatriates who arrived for permanent residence were provided with housing by local authorities and became actively involved in agricultural and construction works. At the same time, the authors note that there were serious shortcomings in the material and domestic arrangements of the Soviet citizens arriving from the PRC. To solve those and other problems, the Agricultural Department of the CPSU Central Committee of the Union Republics sent responsible party and state officials to the Kazakh SSR. Together with the local regional and district authorities, they travelled to the areas where the repatriates were settled and compiled reports and memoranda on the real material and domestic situation of the repatriates. The comprehensive recommendations of the inspection bodies to solve the problems of returnees were voluminous and often difficult to implement. The authors conclude that the issues of housing and employment of repatriates from the PRC were not fully solved due to objective and subjective reasons.
Keywords: history of Kazakhstan; development of virgin lands; repatriates; citizens arriving from the People’s Republic of China